1
2
3
4
5
6
7
8
Solve -3 = x + x + x.
-5
-1
-1

Question

Asked 3/24/2014 2:10:48 PM

Updated 5/30/2014 9:38:00 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by yeswey [5/30/2014 9:37:39 AM]

roshnirazilee|Points 100|

jher000|Points 8066|

eturker|Points 3067|

N = 2

Question

Asked 3/24/2014 2:10:48 PM

Updated 5/30/2014 9:38:00 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by yeswey [5/30/2014 9:37:39 AM]

Rating

3

-3 = x + x + x

-3 = 3x

x = -3/3

x = -1

-3 = 3x

x = -3/3

x = -1

Added 5/30/2014 9:38:00 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/30/2014 9:38:27 AM]

5(x + 1) = 4(x + 8)
x = 7
x = 17
x = 27
x = 37 User: Solve for x.
5(x + 1) = 4(x + 8)
x = 7
x = 17
x = 27
x = 37 User: Simplify the given equation.
6 - (3x + 10) + 4(2 - x) = 15
4 - 7x = 15
4 - 4x = 15
12 - 7x = 15 **Weegy:** A.4 - 7x = 15 **User:** Solve for x.
5(x - 3) + 4(x + 3) = 3(x - 1)
x = 0
x = 1/4
x = 1/2
x = 1 **Weegy:** A.4 - 7x = 15 **User:** Solve for x.
5(x - 3) + 4(x + 3) = 3(x - 1)
x = 0
x = 1/4
x = 1/2
x = 1 **Weegy:** A.4 - 7x = 15 **User:** Solve for x.
7(x - 3) + 3(4 - x) = -8
x = 1/4
x = 25/10
x = -16/19
x = -41/10 **Weegy:** D.x = 44 **User:** Solve for x.
3(x + 2) = 12 **User:** Solve for x.
7(x + 2) = 6(x + 5)
**Weegy:** this is true for X if the value of X=4 or less. **User:** Solve for x.
7(x + 2) = 6(x + 5)
x = -44
x = -16
x = 16
x = 44 **Weegy:** D.x = 44 **User:** 5(x - 3) + 4(x + 3) = 3(x - 1)
x = 0
x = 1/4
x = 1/2
x = 1 **Weegy:** (x + 0.2)(x - 0.2) x^2 + 0.2x - 0.2x - 0.04 = x^2 - 0.04 **User:** Solve for x.
5(x - 3) + 4(x + 3) = 3(x - 1) **Weegy:** 9 + 5(2 - x) - 3 (x +15)
= -8x - 26 **User:** Solve for x.
3(x + 2) = 12 **User:** Solve for b.
ab + c = d
b = a + c/d
b = a/(c - d)
b = (d - c)/a (More)

Question

Not Answered

Updated 3/24/2014 7:52:54 PM

4 Answers/Comments

5(x - 3) + 4(x + 3) = 3(x - 1)

5x - 15 + 4x + 12 = 3x - 3

9x - 3 = 3x - 3

9x - 3x = -3 + 3

6x = 0

x = 0

5x - 15 + 4x + 12 = 3x - 3

9x - 3 = 3x - 3

9x - 3x = -3 + 3

6x = 0

x = 0

Added 3/24/2014 7:49:15 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [3/24/2014 8:06:28 PM]

7(x - 3) + 3(4 - x) = -8

7x - 21 + 12 - 3x = -8

4x - 9 = -8

4x = -8 + 9

4x = 1

x = 1/4

7x - 21 + 12 - 3x = -8

4x - 9 = -8

4x = -8 + 9

4x = 1

x = 1/4

Added 3/24/2014 7:50:47 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [3/24/2014 11:28:48 PM]

3(x + 2) = 12

3x + 6 = 12

3x = 12 - 6 = 6

x = 6/3 = 2

3x + 6 = 12

3x = 12 - 6 = 6

x = 6/3 = 2

Added 3/24/2014 7:51:38 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [3/24/2014 11:28:51 PM]

27,928,964

questions answered

There are no comments.